Comparison of Clinical Isolates of Aeromonas from Singapore and Malaysia with Regard to Molecular Identification, Virulence, and Antimicrobial Profiles - Khor, Wei Ching; Puah, Suat Moi; Koh, Tse Hsien; Tan, Jin Ai Mary Anne; Puthucheary, Savithri Devi; Chua, Kek Heng (Mary Ann Liebert, 2018)
RESULTS: Of the 210 Aeromonas isolates, A. dhakensis-94 (45%) was the dominant species in Singapore and Malaysia. Species composition was similar and enterobacterial repetitive intergenic consensus-PCR did not show genetic relatedness between strains from the two countries. Of the 15 virulence genes, A. dhakensis and A. hydrophila harbored the most compared with other species. Different combinations of 9 virulence genes (exu, fla, lip, eno, alt, dam, hlyA, aexU, and ascV) were present in A. dhakensis, A. hydrophila, and A. veronii from both the countries. Distribution of virulence genes was species and anatomic site related. Majority (>80%) of the strains were susceptible to all antimicrobial agents tested, except amoxicillin and cephalothin. A. dhakensis strains from Malaysia significantly harbored the cphA gene compared with A. dhakensis from Singapore. Multidrug resistance was mostly detected in strains from peritoneal fluids of dialysis patients.